Rabies Cases in the West of China Have Two Distinct Origins. - Xiao-Yan Tao; Zhen-Yang Guo; Hao Li; Wen-Tao Jiao; Xin-Xin Shen; Wu-Yang Zhu; Simon Rayner; Qing Tang (Public Library of Science (PLoS), 2015)
In China, rabies remains an ongoing threat to public health. Although control efforts have been effective in reducing the number of annual cases, the virus continues to spread into new areas. Tibet, Qinghai, Gansu and Ningxia in western China have, until recently, reported only a handful of events. However, since 2011, there have been increasing numbers of cases recorded in these areas. In this study, we report the collection and analysis of samples collected from these regions. We find that cases originate from two different sources. Strains collected from Gansu and Ningxia are closely related to the primary lineage associated with the current epizootic, whereas those from Tibet and Qinghai are related to the Arctic-like-2 lineage that is most commonly associated with wildlife cases in China. Thus, it appears that while the epizootic is beginning to encroach into Gansu and Ningxia, Tibet and Qinghai a significant number of rabies cases originate from wildlife.